2015
DOI: 10.1186/s13059-015-0677-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid draft sequencing and real-time nanopore sequencing in a hospital outbreak of Salmonella

Abstract: BackgroundFoodborne outbreaks of Salmonella remain a pressing public health concern. We recently detected a large outbreak of Salmonella enterica serovar Enteritidis phage type 14b affecting more than 30 patients in our hospital. This outbreak was linked to community, national and European-wide cases. Hospital patients with Salmonella are at high risk, and require a rapid response. We initially investigated this outbreak by whole-genome sequencing using a novel rapid protocol on the Illumina MiSeq; we then int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
233
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(241 citation statements)
references
References 31 publications
0
233
0
2
Order By: Relevance
“…Furthermore, recent updates in nanopore sequencing technology that became commercially available in late 2016 made it possible to obtain gigabases of sequence data from a single flowcell. Prior to this, due to relatively low output, the nanopore sequencing technology was mainly used to analyze and assemble microbial samples (Loman et al, 2015;Quick et al, 2015;Jain et al, 2016;Kranz et al, 2017). Notably, early reports of Oxford nanopore reads indicate that they are exceptionally long (Weirather et al, 2017) but have a high (Judge et al, 2015), and nonrandom, error rate (Deschamps et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent updates in nanopore sequencing technology that became commercially available in late 2016 made it possible to obtain gigabases of sequence data from a single flowcell. Prior to this, due to relatively low output, the nanopore sequencing technology was mainly used to analyze and assemble microbial samples (Loman et al, 2015;Quick et al, 2015;Jain et al, 2016;Kranz et al, 2017). Notably, early reports of Oxford nanopore reads indicate that they are exceptionally long (Weirather et al, 2017) but have a high (Judge et al, 2015), and nonrandom, error rate (Deschamps et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that only WGS has the capability to fulfill all of these features and has already been used, or shown to be potentially useful, for epidemiological (and potentially diagnostic) investigation [4][5][6][7][8][9][10][11][12]. In what is a transformation in microbiology, Public Health England (PHE) has sequenced a total of approximately 50,000 bacterial and viral genomes with resulting improved surveillance and outbreak investigations and intends to harness its full potential in supporting the NHS to deliver the best care for patients [13].…”
Section: The Case For Whole Genome Sequencing (Wgs)mentioning
confidence: 99%
“…Its portability and capacity to perform real-time analysis during sequencing has made it an attractive companion for outbreak investigations in remote regions, as was the case with the ZIBRA project 29 . Clinically, MinION sequencing has been used to retrospectively analyse S. enterica isolates in relation to a European-wide outbreak 30 , which showed that the outbreak strain could be identified from less than 2 hours of sequencing, despite not having the resolution to elucidate transmission pathways. Viral pathogens have also been identified from clinical metagenomic samples, with a projected turn-around time of less than 6 hours 31 .…”
Section: Nanopore: a New And Emerging Technology For Real-time Analysismentioning
confidence: 99%